Heparin-Induced Ecchymosis Following Intravenous Unfractionated Heparin Therapy: A Case Report - Sudais, Mohamed; Ravi, Priyadharsini; Ismail, Rabiyath Riswana (Indian Journal of Pharmacy Practice, 2026)
Heparin is one of the most widely used anticoagulants for the prevention and treatment of thromboembolic disorders. Although bleeding complications and thrombocytopenia are well-recognized adverse effects, cutaneous manifestations such as ecchymosis are relatively uncommon and may be underreported in clinical practice. A 75-year-old female with a history of type 2 diabetes mellitus, systemic hypertension, chronic kidney disease, and Parkinson’s disease presented with breathlessness, palpitations, and generalized weakness. She was diagnosed with accelerated hypertension, acute pulmonary edema, atrial fibrillation, and acute left ventricular failure. Following administration of intravenous unfractionated heparin (4000 IU), the patient developed a large, painless, non-blanching ecchymotic patch measuring more than 10 cm in diameter on the right forearm within five hours of exposure. There was no prior history of drug allergy or cutaneous adverse reactions. Based on the temporal relationship between drug administration and lesion development, a causality assessment was performed using the Naranjo Adverse Drug Reaction Probability Scale. The patient achieved a score of 8, indicating probable adverse drug reaction to heparin. The lesion was managed conservatively and monitored closely. During follow-up, no progression of the lesion was observed, and gradual resolution occurred over the subsequent days without additional complications. This case highlights a rare manifestation of heparin-induced ecchymosis in an elderly patient with multiple comorbidities and emphasizes the importance of recognizing uncommon cutaneous adverse reactions associated with anticoagulant therapy. Healthcare professionals should maintain a high index of suspicion for unusual skin manifestations following heparin administration. Early recognition and appropriate monitoring are essential to prevent misdiagnosis and to exclude serious complications such as heparin-induced thrombocytopenia.
Keywords: Adverse Drug Reaction; Anticoagulant Therapy; Cutaneous Reaction; Ecchymosis; Heparin